A PRELIMINARY NOTE ON A SUBFOSSIL FAUNA OF SMALL VERTEBRATES ON AN OLD DELTA IN THE REGION OF ZUMPANGO MEXICO - MALDONADO KOERDELL, MANUEL (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1948)
Total beta-amylase was studied by a modification of Miller and Sandstedt's method; protease activity was detd first in the dry seed and then in undried germinated ones, by the Waldschmidt-Leitz method Saccharogenic activity increased up to the 10th day
REV SOC MEX HIST NAT
Keywords: PRELIMINARY NOTE, SUBFOSSIL FAUNA, SMALL VERTEBRATES, OLD DELTA, REGION OF ZUMPANGO MEXICO; CIENCIAS DE LA VIDA; PALEONTOLOGIA; PALEONTOLOGIA DE LOS INVERTEBRADOS